88.1k views
5 votes
Answer these three questions for 100 points

Question 1) Identifying the values a, b, and c is the first step in using the Quadratic Formula to find solution(s) to a quadratic equation.

What are the values a, b, and c in the following quadratic equation?

−6x2 = −9x + 7

A) a = 9, b = 7, c = 6
B) a = −9, b = 7, c = −6
C) a = −6, b = 9, c = −7
D) a = −6, b = −9, c = 7

Question 2) Identifying the values a, b, and c is the first step in using the Quadratic Formula to find solution(s) to a quadratic equation.

What are the values a, b, and c in the following quadratic equation?

−6x2 − 8x + 12 = 0

A) a = −6, b = −8, c = 12
B) a = 6, b = 8, c = 12
C) a = 8, b = 12, c = 0
D) a = −8, b = 12, c =

Question 3) The quadratic equation 4x2 + 45x + 24 = 0 was solved using the Quadratic Formula, x equals negative b plus or minus the square root of b squared minus 4 times a times c, all over 2 times a.

One solution is −10.69. What is the other solution? Round to the hundredths place.

A) 0.51
B) 10.69
C) −1.12
D) −0.56

2 Answers

2 votes

Answer: C, A, D

edit - sorry the title was wrong earlier

Explanation:

Question 1

in the quadratic formula, the equation is in the format of ax^2 + bx + c

so rearrange this equation so all values are on one side

-6x^2 = -9x + 7

-6x^2 + 9x - 7 =0

so a = -6, b = 9, c = -7

answer = C

Question 2

note that all the values are already on one side for this, so repeat the process from question 1 where the equation is in the format of ax^2 + bx + c

the equation = −6x2 − 8x + 12 = 0

so a = -6, b = -8, c = 12

answer = A

Question 3

(see picture below for steps)

following the same process above, a = 4, b = 45, and c = 24, so plug these values in the quadratic equation shown in the picture below

so you get the answers x = -10.69 and x = -0.56 after putting them in a calculator

answer = D

Answer these three questions for 100 points Question 1) Identifying the values a, b-example-1
User RNK
by
5.1k points
5 votes

Answer:

Q1) C

Q2) A

Q3) D

Explanation:

Q1)

-6x² = -9x + 7

-6x² + 9x - 7 = 0

a = -6, b = 9, c = -7

Q2)

−6x2 − 8x + 12 = 0

a = -6, b = -8, c = 12

Q3)

4x² + 45x + 24 = 0

Sum of roots = -b/a

Sum = -45/4 = -11.25

Let the other root be x

x + (-10.69) = -11.25

x = -11.26 + 10.69

x = -0.56

User Drarok
by
5.7k points